Voting transparency and conflicting interests in central bank councils - Gersbach, Hans; Hahn, Volker (Discussion paper, 2001)
This paper examines whether it is socially desirable for the individual voting records of central bank council members to be published when central bankers' ; preferences differ. We show that the misrepresentation of their preferences is not advantageous for central bankers although central bankers take into account the fact that they might not be re-elected. Thus, the publication of voting records is beneficial since the government can distinguish central bankers' ; in terms of their preferences and can align the central bank council's preferences with those of the general public over time by means of its re-election decisions.
Zsfassung in dt. Sprache. - Literaturverz. S. 15 - 16
Keywords: Arbeitspapier; Graue Literatur; Publizitätspflicht; Abstimmung; Beschlussfassung; Notenbank